SISTEM AKUNTANSI ASET TETAP - Mawardahny Isyabilla; Nobert Nathanael Saragih; Syarifah Ghizka Safitri (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2024)
Fixed assets are an essential component of a company as they provide long-term economic benefits and play a crucial role in supporting operational activities. The management of fixed assets requires an adequate accounting system to ensure accurate recording, effective control, and reliable financial reporting. This article aims to examine the fixed asset accounting system as part of the accounting information system, including the definition and characteristics of fixed assets, transactions affecting fixed assets, supporting documents, and the internal control elements applied. The method used in this study is a literature review by examining relevant accounting literature and standards, combined with a conceptual analysis of fixed asset accounting system procedures. The discussion results indicate that the implementation of a well-structured fixed asset accounting system, supported by adequate documentation and effective internal control, can improve the accuracy of asset records, minimize the risk of errors and fraud, and produce more reliable financial statements. Therefore, the fixed asset accounting system plays a strategic role in supporting managerial decision-making and corporate financial accountability. Keywords: fixed assets, fixed asset accounting system, accounting information system, internal control, financial statements